TAHFIDZUL QUR’AN SEBAGAI UPAYA PENINGKATAN NILAI-NILAI EMOTIONAL SPIRITUAL QUOTIENT SANTRI PUTRI PPTQ BAITUL ‘ABIDIN DARUSSALAM SARIMULYO KALIBEBER MOJOTENGAH WONOSOBO TAHUN 2018 - Tholhatur Rif’ah; Abdurrahman Asy’ari; Muhammad Najib Al-Adib (Pendidikan Agama Islam (S2), UNSIQ Wonosobo, Jawa Tengah, 2019)
A classic tendency throughout human history, that intellectual conflicts sometimes occur because of separation, example IQ which is separate from SQ, and EQ that is divorced from SQ. This proves that the importance of making efforts to increase in order to develop emotional intelligence and spiritual intelligence. This intelligence is an embodiment of integration between relationship with God and relationship with human, in other words (hablumminallah and hablumminannas). That is, there is a transfer of values from ritual behavior to daily life and social behavior. This research aims to 1) Know the activities of memorizing al-Qur’an for female Islamic students of PPTQ Baitul ‘Abidin Darussalam 2) Know the emotional and spiritual intelligence of female Islamic students at the PPTQ Baitul ‘Abidin Darussalam 3) Know the form of increasing the values of emotional and spiritual intelligence through memorizing activities the al-Qur’an of female Islamic students at PPTQ Baitul ‘Abidin Darussalam. This is field research in the form of qualitative research that is descriptive analytically with an andragogical approach. As needed, data collection was carried out by the method of observation, interviews, questionnaires and documentation. Furthermore, the data obtained were analyzed by data reduction, data presentation and data verification. The results of the study showed that the activities of memorizing the al-Qur’an of female Islamic students carried out at the PPTQ Baitul ‘Abidin Darussalam can increase the values of emotional and spiritual intelligence. Based on the data obtained that through the practice of riyadhah ‘well-behaved’ female Islamic students in the process of memorizing the Qur'an such as Qiyamullail; Prayer; Fasting (sunah); Thingking of God (ẓikir); Preserves the Wuḍu; Tooth Brush; and Time Management can develop the level of female Islamic students’ self-potential. As for the value of ‘self-potential’ among other: integrity, allegiance, laughter, honesty, responsibility, cooperation, fairness, caring, visionary, patient, himmatul khasanah, sincerity, kaffah, discipline, commitment, consistency, gratitude and always think positively